Aging of Dry Desiccation-Tolerant Pollen Does Not Affect Protein Secondary Structure. - Wolkers, W. F. (1995)
Protein secondary structure and membrane phase behavior in aging Typha latifolia pollen were studied by means of Fourier transform infrared microspectroscopy (FTIR). Membranes isolated from fresh pollen occurred mainly in the liquid crystalline phase at room temperature, whereas the membrane fluidity of aged pollen was drastically decreased. This decrease did not result in large-scale irreversible protein aggregation, as was concluded from in situ FTIR assessment of the amide-1 bands. Curve-fitting on the infrared absorbance spectra enabled estimation of the proportion of different classes of protein secondary structure. Membrane proteins had a relatively large amount of [alpha]-helical structure (48%; band at 1658 cm-1), and turn-like structures (at 1637 and 1680 cm-1) were also detected. The secondary protein structure of isolated cytoplasmic proteins resembled that of proteins in whole pollen and was conserved upon drying in the absence of sucrose. The isolated cytoplasmic proteins had a large amount of [alpha]-helical structure (43%), and also [beta]-sheet (at 1637 and 1692 cm-1) and turn structures were detected. Heat-denaturing experiments with intact hydrated pollen showed low (1627 cm-1) and high (1692 cm-1) wave number bands indicating irreversible protein aggregates. The results presented in this paper show that FTIR is an extremely suitable technique to study protein secondary structure in intact plant cells of different hydration levels and developmental stages.